2016
DOI: 10.1007/s12639-016-0793-2
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of benzimidazole resistant and susceptible isolates of Haemonchus contortus from sheep by allele specific PCR

Abstract: Extensive and indiscriminate use of the benzimidazole class of drugs has led to the onset of anthelmintic resistance. In tropical countries like India, Haemonchus contortus is the most pathogenic parasite infecting sheep and goats. The widespread presence of resistant helminths (especially H. contortus) threatens the livestock farming. The use of various drugs has led to single nucleotide polymorphism that causes specific amino acid substitutions in b-tubulin protein of H. contortus to confer resistance. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…The results show that SNP at 200 is more prevalent than the other two SNPs in India. The result of the present study is in accordance with the previous reports of Mohanraj et al (2017) and other researchers, who reported mutation at codon 200 of β-tubulin by allele-specific PCR in H. contortus of Tamil Nadu and Uttar Pradesh [9,10,30]. H. contortus, Bunostomum trigonocephalum, T. circumcincta, and Trichostrongylus colubriformis β-tubulin isotype 1 of small ruminants of Uttarakhand showed a prevalence of SNP at position 200 of β-tubulin isotype 1 by allele-specific PCR [31,32,33].…”
Section: Resultssupporting
confidence: 94%
“…The results show that SNP at 200 is more prevalent than the other two SNPs in India. The result of the present study is in accordance with the previous reports of Mohanraj et al (2017) and other researchers, who reported mutation at codon 200 of β-tubulin by allele-specific PCR in H. contortus of Tamil Nadu and Uttar Pradesh [9,10,30]. H. contortus, Bunostomum trigonocephalum, T. circumcincta, and Trichostrongylus colubriformis β-tubulin isotype 1 of small ruminants of Uttarakhand showed a prevalence of SNP at position 200 of β-tubulin isotype 1 by allele-specific PCR [31,32,33].…”
Section: Resultssupporting
confidence: 94%
“…These hypotheses are consistent with the results obtained previously by our group when we evaluated codons 167 and 198 of some of these same samples [11]. If these populations had been subjected to frequent treatments, probably SNPs linked to benzimidazole resistance would be more frequent, as described for other parasite populations [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence observed in our results is lower than the prevalence reported for veterinary parasites, as in H . contortus [29,30]. However, in some studies that analyzed these SNPs in ascarids of veterinary importance (i.e P .…”
Section: Discussionmentioning
confidence: 99%
“…Molecular diagnostic tests have been demonstrated for multiple benzimidazole (BZ) resistance SNPs in parasitic nematodes using various methodologies, including allele specific (AS)-PCR, restriction fragment length polymorphism (RFLP), and pyrosequencing ( Winterrowd et al, 2003 ; Tiwari et al, 2006 ; von Samson-Himmelstjerna et al, 2009 ; Mohanraj et al, 2017 ). A recent development in large scale surveillance is the ‘Nemabiome’ approach, which makes use of deep amplicon sequencing of barcoded PCR products ( Avramenko et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%